A FE2 modelling approach to hydromechanical coupling in cracking-induced localization problems. (15th October 2016) - van den Eijnden, A.P.; Bésuelle, P.; Chambon, R.; Collin, F.
Abstract: An approach to multiscale modelling of the hydro-mechanical behaviour of geomaterials in the framework of computational homogenization is presented. At the micro level a representative elementary volume (REV) is used to model the material behaviour based on the interaction between a solid skeleton and a pore fluid to provide the global material responses and associated stiffness matrices. Computational homogenization is used to retrieve these stiffness matrices from the micro level. The global response to deformation of the REV serves as an implicit constitutive law for the macroscale. On the macroscale, a poro-mechanical continuum is defined with coupled hydro-mechanical behaviour, relying on the constitutive relations obtained from the modelling at the microscale. This double scale approach is applied in the simulation of a biaxial deformation tests and the response at the macro level is related to the micro-mechanical behaviour. Hydromechanical coupling is studied as well as material anisotropy. To be able to study localization of strain, the doublescale approach is coupled with a local second gradient paradigm to maintain mesh objectivity when shear bands develop.